HOspitals and patients WoRking in Unity (HOW R U?): protocol for a prospective feasibility study of telephone peer support to improve older patients' quality of life after emergency department discharge. Issue 12 (2nd December 2016) - Lowthian, Judy A; Lennox, Alyse; Curtis, Andrea; Dale, Jeremy; Browning, Colette; Smit, De Villiers; Wilson, Gillian; O'Brien, Debra; Rosewarne, Cate; Boyd, Lee; Garner, Cath; Cameron, Peter
Abstract : Introduction: Older people presenting to an emergency department (ED) have a higher likelihood of social isolation, loneliness and depression; which are all associated with negative health outcomes and increased health service use, including higher rates of ED attendance. The HOW R U? study aims to ascertain the feasibility and acceptability of a postdischarge telephone support programme for older ED patients following discharge. The intervention, which aims to improve quality of life, will be delivered by hospital-based volunteers. Methods and analysis: A multicentre prospective uncontrolled feasibility study will enrol 50 community-dwelling patients aged ≥70 years with symptoms of loneliness or depression who are discharged home within 72 hours from the ED or acute medical ward. Participants will receive weekly supportive telephone calls over a 3-month period from a volunteer-peer. Feasibility will be assessed in terms of recruitment, acceptability of the intervention to participants and level of retention in the programme. Changes in level of loneliness (UCLA-3 item Loneliness Scale), mood (Geriatric Depression Scale-5 item) and health-related quality of life (EQ-5D-5L and EQ-VAS) will also be measured postintervention (3 months). Ethics and dissemination: Research ethics and governance committee approval has been granted for this study by each participating centre (reference: 432/15 and 12-09-11-15). Study findings will inform the design and conduct of a future multicentre randomised controlled trial of a postdischarge volunteer-peer telephone support programme to improve social isolation, loneliness or depressive symptoms in older patients. Results will be disseminated through peer-reviewed journal publication, and conference and seminar presentation. Trial registration number: ACTRN12615000715572, Pre-results.